Evaluation of a pediatric post-acute sequelae of SARS-CoV-2 index score - Dun-Dery, Frederick; Xie, Jianling; Winston, Kathleen; Burstein, Brett; Sabhaney, Vikram; Emsley, Jason; Gravel, Jocelyn; Kam, April; Beer, Darcy; Zemek, Roger; Mater, Ahmed; Porter, Robert; et al. (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to assess the performance of the Researching COVID-19 to Enhance Recovery (RECOVER) initiative's proposed post-acute sequelae of COVID-19 (PASC) index in a cohort of children evaluated for SARS-CoV-2 infection, 6–12 months after exposure.Study designWe conducted a multicenter, prospective cohort study with 6- and 12-month follow-up in 14 Canadian tertiary-care pediatric emergency departments (EDs) in the Pediatric Emergency Research Canada network. Eligible children were 6 to <18 years of age who were tested for acute SARS-CoV-2 infection. We assessed the score validity and reliability and evaluated the associations between PASC index scores dichotomized using threshold values (≥5.5 for ages 6 to <12 years and ≥5.0 for ages 12 to <18 years) and SARS-CoV-2 infection.ResultsParticipants included 785 children, with a median age of 9 years (IQR: 7–13), enrolled between August 2020 and February 2022. Factor analysis identified characteristics that accounted for 32%–40% of variance. Strong correlations were identified between PASC index scores and PedsQL™ and overall health status; Cronbach's α ranged from 0.49 to 0.67. Changes in PASC index scores across time points accounted for 71% (6 to <12 years) and 63% (12 to <18 years) of total variance. The proportion of children exceeding PASC index score thresholds did not differ between children positive and negative for SARS-CoV-2 test in the 6 to <12 (25% vs. 22%; aOR: 1.2; 95% CI: 0.6, 2.5) and 12 to <18 (18% vs. 10%; aOR: 2.2; 95% CI: 0.5, 10.4) age groups at 6 months. Similar results were reported at 12 months.ConclusionsWhile scores correlated with quality of life and overall health, internal reliability was low to acceptable. The PASC index was not associated with previous SARS-CoV-2 infection.